Postoperative abdominal sepsis: imaging and percutaneous management. Issue 11 (November 2015) - Renwick, Ian
Abstract: Postoperative abdominal sepsis can now largely be managed non-surgically via drains inserted percutaneously. This article reviews the imaging of abdominal sepsis, the decision making process for its management and the techniques that can be employed for insertion of drains radiologically.